The Effect of Human Resources Development on Employee Performance at Government Office in South Sumatra - Alamsyah, Alamsyah; Elisabet Hamboer, Maria Jashinta; Pranawukir, Iswahyu (Mediastima, 2023)
This study aims to determine the effect of Human Resource Development on Employee Performance in South Sumatra city government offices. The type of research used in this research is explanatory research, to analyze the influence between the variables Human Resource Development (X) with employee performance variable (Y), using a quantitative approach. Data collection techniques using questionnaires and documentation with a simple linear regression analysis method. The results of this study indicate that there is a positive and significant influence between the Human Resource Development variable on Employee Performance at the city government offices of South Sumatra, based on the results of the t test obtained tcount 2.377 > ttable 1.992, Sig test. 0.020 <probability of 0.05, and the results of the coefficient of determination (R Square) indicate that the total influence of the Human Resource Development variable on Employee Performance is 6.3%. This positive influence means that the increase in the Human Resource Development of an employee will affect the increase in the Employee's Performance.